Dynamic optimization management of the dual-credit policy for passenger vehicles. (10th March 2020) - Li, Yaoming; Zhang, Qi; Tang, Yanyan; Mclellan, Benjamin; Ye, Huiying; Shimoda, Hiroshi; Ishihara, Keiichi
Abstract: The dual-credit policy for passenger vehicles was implemented in China in 2018 to continue to nurture the growth of new energy vehicles and effectively alleviate the government's financial subsidy pressure. The policy innovatively introduced the cap-and-trade system into the transport sector and has achieved an initial success in a short term. However, from a long-term viewpoint, there is still a need to formulate the annual percentage targets for new energy vehicle credits to ensure its ongoing sustainable development. To investigate this issue, a multi-period credit market dynamic equilibrium model was developed. Four scenarios, including a decelerated growth scenario, an accelerated growth scenario, a constant growth scenario and a benchmark scenario with a constant percentage, were proposed, in order to comprehensively reflect the changes in new energy vehicle production, credit performance and profits of automakers under different growth scenarios. Compared from the perspectives of automakers and the government, the obtained results showed that: (1) increasingly stricter new energy vehicle credit targets can slow down the growth of internal combustion engine vehicle production and promote substantial growth of new energy vehicles; (2) without the adjustment of the rules of credit calculation, increasingly more stringent new energy vehicle credit targets will be harmful to energy saving goals of corporate average fuel consumption credit management; (3) with the realization of scale advantages and the maturity of battery technology, new energy vehicles could achieve cost-effective breakeven points; (4) from the perspective of new energy vehicle promotion cost, the lowest cost can be achieved in the accelerated growth scenario. Highlights: Dynamic optimization management of the dual-credit policy for passenger vehicles was analyzed. A multi-period credit market dynamic equilibrium model was proposed and developed. The impact of the dual-credit policy on energy saving goals of CAFC credit management was discussed. NEVs could achieve cost-effective breakeven points. Lowest NEV promotion cost can be obtained in accelerated growth scenario.